UJI DAYA HAMBAT EKSTRAK ETANOL PROPOLIS LEBAH TRIGONA ITAMA TERHADAP SALMONELLA TYPHI - Isna Wardaniati; Ardian Sabar Siregar (Jurnal Ilmu Kesehatan Abdurrab, 2023)
Trigona bee is an original animal of Asia and produces propolis. Propolis is used to cover hexagonal space cells in honeycomb, the main components of propolis are resins (flavonoids, phenolic acids and esters) or plant sap collected by bees. Propolis is useful as an antioxidant, antimicrobial, anti-inflammatory, anti-bleeding, anti-tumor, antihistamine, antifungal, strengthens blood vessels, and antiviral. This study aims to determine the inhibitory power of ethanol extract propolis from Trigona itama against Salmonella typhi, was conducted by diffusion method of disc diffusion in MHA media with chloramphenicol as a positive control and DMSO as a negative control. Extraction was carried out by maceration method using 96% ethanol. The extract obtained was diluted to 80%, 60%, and 40% using DMSO with multilevel dilution. The results showed the inhibition zone of the ethanol extract propolis Trigona itama against Salmonella typhi with concentrations of 80%, 60%, and 40% with an average of 14.44 mm, 12.28 mm, and 10.83 mm, and cloramphenocol of 24.31